The relationship between pan-immune inflammation value and different stages of diabetic retinopathy in patients with type 2 diabetes mellitus: a prospective cross-sectional study - Aykut Bulu; Sinem Keser (BMC Endocrine Disorders)
Abstract Background Diabetic retinopathy (DR), a major complication of type 2 diabetes mellitus (T2DM), remains a growing global health concern. This study aimed to evaluate the relationship between systemic inflammatory markers and both the presence and severity of DR. Special attention was given to the pan-immune-inflammation value (PIV), a novel composite index of immune response, whose association with DR remains underexplored. Materials and methods A prospective cross-sectional study was conducted involving 310 patients with T2DM, grouped based on the International Clinical Diabetic Retinopathy Disease Severity Scale (ICDR): no DR (NDR, n = 100), non-proliferative DR (NPDR, n = 100), and proliferative DR (PDR, n = 110). Clinical and laboratory data—including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), neutrophil-to-HDL cholesterol ratio (NHR), systemic immune-inflammation index (SII), and PIV—were analyzed. Statistical methods included ANOVA, Kruskal-Wallis, and receiver operating characteristic (ROC) analyses. Results PDR patients had significantly elevated NLR (p = 0.005), MLR (p < 0.001), NHR (p = 0.016), C-reactive protein-to-albumin ratio (CAR) (p < 0.001), and PIV (p = 0.002) levels. In NPDR, PLR (p = 0.012) and SII (p = 0.005) were significantly higher than in the other groups. NLR showed the highest predictive performance in ROC analysis (sensitivity: 84.8%), followed by SII (78.1%), PLR (76.2%), and PIV (53.3%). Conclusion Among patients with T2DM, inflammatory markers—particularly NLR, PLR, SII, and PIV—suggested potential relevance in identifying DR and its progression. PLR and SII may have utility in the early identification of NPDR, while PIV appears to be a potentially valuable inflammatory marker. These cost-effective and easily accessible indices may contribute to the screening and monitoring of DR in clinical settings.